Protocolo para o cuidar de crianças e adolescentes com transtornos mentais a partir do processo de enfermagem - Landim, Valquiria Mira (2023)
Introduction: A large part of the population is composed of children and adolescents, a considerable part of which are affected by some type of mental disorder that affects their psychological, behavioral, and emotional development. Objective: To build and validate a health protocol that directs the Nursing Process to children and adolescents with mental disorders. Method: This was a methodological study. For the construction of a protocol for carrying out the Nursing Process, a search was carried out for national and international articles published between the years 2011 to 2021, indexed in the Scielo, Web Of Sience, Pubmed, Cinahl, BVS Portal on Process databases. of Nursing to children and adolescents with mental disorders. Elaboration of a protocol with 40 items, based on the elaborated review, and developed in all its stages, presenting Nursing History, Nursing Diagnosis, Planning, Implementation and Evaluation. It was divided into 2 periods: Construction of the Instrument, and afterwards, an invitation was sent to the nurses to participate in the evaluation as judges. The protocol was evaluated for 4 items: Validity, Clarity, Relevance, and Content Comprehensiveness. The results were analyzed by calculating the Content Validity Index (CVI). Results: The protocol was evaluated by a group of 6 judges, namely: 5 professor nurses and 1 nurse coordinator, among the judges all worked in public institutions. The age ranged from 31 to 60 years, with an average training time of 21.6 years. The CVI was 0.99. Most of the changes suggested by the judges were met, and were related to the replacement of terms, nursing diagnoses, inclusion of deadlines for carrying out prescriptions, objectivity in the questions. Conclusion: We hope that this health protocol will guide nursing care for children and adolescents with evidence of mental disorders to standardize care behaviors, qualify nursing care for these children/adolescents, and ensure safety in their work.